2000
DOI: 10.1117/12.391771
|View full text |Cite
|
Sign up to set email alerts
|

<title>TOD predicts target acquisition performance for staring and scanning thermal imagers</title>

Abstract: Identification and recognition performance for four staring and two sc¿nning thermal imagers, \ryere measured in an observer experiment using images lhai were collected during a NATO freld trial in Nettuno, Italy, in 1998. The dataset allows validation of the MRTD and altemative sensor performance measures such as the TODI'2 (Triangle orientation Discrimination threshold). T\e 75%o correct Target Acquisition (TA) râñges were compared with the TOD sensor acuity and the MRTD spatial frequency at ÂT = 2 K. range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…between cooled and uncooled cameras. This is also shown experimentally by Bijl, Valeton & de Jong 12 .…”
Section: Standard Four-bar Pattern 1: Conventional Mrtdsupporting
confidence: 70%
“…between cooled and uncooled cameras. This is also shown experimentally by Bijl, Valeton & de Jong 12 .…”
Section: Standard Four-bar Pattern 1: Conventional Mrtdsupporting
confidence: 70%
“…So it is implicitly assumed that the shape of the MRTD-ID, MRTD-Rec or MTDP curves matches that for real targets. Bijl and Valeton 7,8 showed that the TOD does not only predict the range differences between well-sampled and under-sampled imagers at high thermal contrasts, but also that the shape of the TOD curve (for a CCD camera) matches the contrast vs. range relationship for real targets very well.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure is not only very similar to the real target acquisition process, it also yields results that are independent of the subjective decision criterion of the observer. The relationship with real target acquisition was validated in several experiments 7,8 . Recently a TOD sensor model 9 was developed that explicitly takes into account non-linear operations such as sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Indigo System Corporation,50 Castilian Drive,Goleta,CA,93117 8. PERFORMING ORGANIZATION REPORT NUMBER…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%
“…Finally, TOD can also be used as the basis for range predictions, and in limited trials, has actually produced better correlation to target-acquisition range than bar-target testing. 8,9 An important distinction between MRT and TOD is the duration of the observers' task. When measuring MRT, the target contrast is gradually adjusted as the observer stares at the imagery.…”
Section: Todmentioning
confidence: 99%